Identification of differentially expressed genes by exposure of methylmercury in neuroblastorna cell line using suppression subtractive hybridization (SSH) - Kim, Youn-Jung; Ryu, Jae-Chun (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2006)
Methylmercury (MeHg), one of the heavy metal compounds, can cause severe damage to the central nervous system in humans. Many reports have shown that MeHg is poisonous to human body through contaminated foods and has released into the environment. Despite many studies on the pathogenesis of MeHg-induced central neuropathy, no useful mechanism of toxicity has been established so far. This study, using of suppression subtractive hybridization (SSH) method, was performed to identify differentially expressed genes by MeHg in SH-SY5Y human neuroblastoma cell line. We prepared to total RNA from SH-SY5Y cells treated with solvent (DMSO) and 6.25 mu M (IC50) MeHg and performed forward and reverse SSH. Differentially expressed cDNA clones were screened by dot blot, sequenced and confirmed that individual clones indeed represent differentially expressed genes with real time RT-PCR. These sequences were identified by BLAST homology search to known genes or expressed sequence tags (ESTs). Analysis of these sequences may provide an insight into the biological effects of MeHg in the pathogenesis of neurodegenerative disease and a possibility to develop more efficient and exact monitoring system of heavy metals as ubiquitous environmental pollutants.
Keywords: ENERGY-METABOLISM; MERCURY; CLONING; TARGET; BRAIN